Reno-Protective Effect of Low Protein Diet Supplemented With α-Ketoacid Through Gut Microbiota and Fecal Metabolism in 5/6 Nephrectomized Mice - Zhu, Yifan; He, Haidong; Tang, Yuyan; Peng, Yinshun; Hu, Ping; Sun, Weiqian; Liu, Ping; Jin, Meiping; Xu, Xudong (Frontiers in Nutrition, 2022)
Background Low-protein supplemented with α-ketoacid diet (LKD) was recommended to be an essential intervention to delay the progression for chronic kidney disease (CKD) patients not yet on dialysis. Aberrant gut microbiota and metabolism have been reported to be highly associated with CKD. However, the effect of LKD on gut microbiota and related fecal metabolism in CKD remains unclear. Methods Mice were fed with normal-protein diet (NPD group), low-protein diet (LPD group), and low-protein diet supplemented with α-ketoacid (LKD group) after 5/6 nephrectomy. At the end of the study, blood, kidney tissues, and feces were collected for biochemical analyses, histological,16S rRNA sequence of gut microbiome, and untargeted fecal metabolomic analyses. Results Both LKD and LPD alleviate renal failure and fibrosis, and inflammatory statement in 5/6 nephrectomized mice, especially the LKD. In terms of gut microbiome, LKD significantly improved the dysbiosis induced by 5/6Nx, representing increased α diversity and decreased F/B ratio. Compared with NPD, LKD significantly increased the abundance of g_Parasutterella, s_Parabacteroides_sp_CT06, f_Erysipelotrichaceae, g_Akkermansia, g_Gordonibacter, g_Faecalitalea, s_Mucispirillum_sp_69 ; and decreased s_Lachnospiraceae_bacterium_28-4, and g_Lachnoclostridium. Moreover, 5/6Nx and LKD significantly altered fecal metabolome. And multi-omics analysis revealed that specific metabolites involved in Glycerophospholipid, Purine,Vitamin B6, Sphingolipid, Phenylalanine, tyrosine and tryptophan biosynthesis and microbes associated with LKD were correlated with the amelioration of CKD. Conclusion LKD had a better effect than LPD on delaying renal failure in 5/6 nephrectomy-induced CKD, which may be due to the regulation of affecting the gut microbiome and fecal metabolic profiles.